Document indexing with a concept hierarchy - Alexander Gelbukh (Computación y Sistemas, 2005)
Given a large hierarchical concept dictionary (thesaurus, or ontology), the task of selection of the concepts that describe the contents of a given document is considered. A statistical method of document indexing driven by such a dictionary is proposed. The method is insensible to inaccuracies in the dictionary, which allow for semi-automatic translation of the hierarchy into different languages. The problem of handling non-terminal and especially top-level nodes in the hierarchy is discussed. Common sense-complaint methods of automatically assigning the weights to the nodes and links in the hierarchy are presented. The application of the method in the Classifier system is discussed.